Adoption of indirect instruments of monetary policy - Alexander, William E...[et al] (IMF WashingtonUS, 1995)
Examines the experience of implementing indirect instruments of monetary policy. Describes the characteristics of direct and indirect instruments and explains the reasons for moving from the former to the latter. Addresses issues in the reform of monetary policy instruments. Examines a number of countries that have adopted indirect instruments and reviews both how they did it and the results. Looks at the implications for the adoption of indirect instruments and discusses the design of IMF-supported stabilization programmes and the need for technical assistance.